E-Government and Its Limitations: Assessing the True Demand Curve for Citizen Public Participation - Karpf, David (AoIR Selected Papers of Internet Research, 2013)
Many e-government initiatives start with promise, but end up either as digital "ghost towns" or as a venue exploited by organized interests. The problem with these initiatives is rooted in a set of common misunderstandings about the structure of citizen interest in public participation – simply put, the Internet does not create public interest, it $2 public interest. Public interest can be high or low, and governmental initiatives can be polarized or non-polarized. The paper discusses two common pitfalls (“the Field of Dreams Fallacy” and “Blessed are the Organized”) that demand alternate design choices and modified expectations. By treating public interest and public polarization as variables, the paper develops a typology of appropriate e-government initiatives that can help identify the boundary conditions for transformative digital engagement.